2008
DOI: 10.1017/s175173110700105x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cobalt and iodine supplementation of the pregnant ewe diet on immunoglobulin G, vitamin E, T3 and T4 levels in the progeny

Abstract: Sixty twin-bearing ewes were allocated to one of four dietary treatments investigating the effects of supplementary iodine or cobalt during late pregnancy on lamb serum immunoglobulin G (IgG), triiodothyronine (T 3 ), thyroxine (T 4 ) and vitamin E concentrations, and lamb IgG absorption efficiency. Ewes were offered grass silage ad libitum supplemented with 800 g per ewe per day of a 190 g/kg crude protein (CP) concentrate from day 126 of gestation until parturition plus one of the following supplements (n 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 41 publications
10
29
0
1
Order By: Relevance
“…Ewes received either the basal diet with no supplementary iodine (Control) or the basal diet plus 26.6 mg/day of iodine supplied as either CaIO 3 or KI (Table 1). This level of supplementary iodine equates to the level offered to ewes in a previously reported study (Boland et al, 2008) and is reflective of the level of intake achieved when ewes are offered free access mineral supplements indoors . In accordance with a previous study, carried out at this institute, the dietary intake of iodine on the control diet can be estimated at~0.57 mg iodine per ewe per day (Boland et al, 2008).…”
Section: Nutritional Treatmentsmentioning
confidence: 60%
See 4 more Smart Citations
“…Ewes received either the basal diet with no supplementary iodine (Control) or the basal diet plus 26.6 mg/day of iodine supplied as either CaIO 3 or KI (Table 1). This level of supplementary iodine equates to the level offered to ewes in a previously reported study (Boland et al, 2008) and is reflective of the level of intake achieved when ewes are offered free access mineral supplements indoors . In accordance with a previous study, carried out at this institute, the dietary intake of iodine on the control diet can be estimated at~0.57 mg iodine per ewe per day (Boland et al, 2008).…”
Section: Nutritional Treatmentsmentioning
confidence: 60%
“…In specific livestock species, low immunoglobulin levels in the newborn have been associated with impaired health in later life, thus emphasising the importance of colostrum for the growth and well-being of the newborn (Speikermann et al, 2002). Previous studies have, however, recently demonstrated a negative relationship between iodine supplementation of the pregnant ewe in late gestation and the serum IgG concentration of her progeny at 24 h postpartum (Boland et al, 2006 and2008;Rose et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations